The inhibitory effects of compound Muniziqi granule against B16 cells and harmine induced autophagy and apoptosis by inhibiting Akt/mTOR pathway - Nan Zou; Yue Wei; Fenghua Li; Yang Yang; Xuemei Cheng; Changhong Wang (BMC, 2017)
Abstract Background Compound Muniziqi granule (MNZQ) is a multi-component herbal preparation and a popular traditional Uighur medicine used in China for treating endocrine disorder-induced acne, chloasma, dysmenorrhea, menopausal syndrome, and melanoma. Harmine presented in MNZQ has been confirmed potential anticancer effect on the B16 cells among others. The purpose of this study is to explore the inhibitory effects of MNZQ against B16 cells and mechanism of autophagy and apoptosis induced by harmine in B16 cells. Methods The cell viability was calculated by CCK8 assay. The in vitro tyrosinase activity was determined by spectrophotometry. The harmine-induced autophagy was demonstrated by electron microscopy and MDC staining. Flow cytometry was used to measure cell death and cell cycle distribution. All proteins expression was assessed by western blot. Results MNZQ and some herb extracts contained in preparation displayed inhibitory effects on B16 cells but without inhibition on mushroom tyrosinase compared with kojic acid. The formation of autophagosome was markedly induced by harmine with the accretion of LC3-II and the degeneration of p62 in B16 cells, which indicated that harmine was an autophagy inducer. Cell death and sub-G2 population suggested that harmine could induce cell death. Particularly, 3-MA, an autophagy inhibitor, was discovered to prevent harmine-induced decrease of the cell viability and cell cycle arrest on G2 phase, indicating that autophagy was vital to the cell death. In addition, the results indicated that harmine could inhibit the phosphorylation of Akt and mTOR, which might mediate autophagy. Conclusion Harmine could induce autophagy and apoptosis by inhibiting Akt/mTOR pathway in B16 cells. Harmine might be a promising therapeutic agent for treatment of melanoma in MNZQ.